THE ROLE OF PHYSICAL CULTURE AND SPORT IN PERSONALITY DEVELOPMENT - Sotivoldiev Qodirjan (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
the article deals with the influence of physical culture on improving well-being, the formation of physical abilities, and the comprehensive development of the individual. Physical culture is considered as a sphere of culture, which allows using its own means and methods to reveal the abilities of a person. The article defines the role of physical culture in the upbringing and self-education of a person, which is achieved only with proper physical education and sports.